Effectiveness of brief online mindfulness-based intervention on different types of mobile phone addiction: mechanisms of influence of trait mindfulness - Zhiyu Zhang; Lei Wu; Lei Wu; Chu Lu; Tianming Guan (Frontiers in Psychology)
IntroductionIt is common for college students to suffer from mobile phone addiction, which can seriously affect their physical and mental health. The current study looked at the impact of a brief online mindfulness-based intervention (MBI) on mobile phone addiction to address this problem. The mechanisms behind the influence of trait mindfulness (TM) on this process were also investigated in the current study.MethodsSubjects were split into two groups for a randomized controlled trial: an experimental group and a control group. During brief online MBI, online assessments of mobile social networking addiction (MSNA), mobile game addiction (MGA), mobile information acquisition addiction (MIAA), and mobile short-form video addiction (MSVA) as well as TM were completed. The present study examined the effectiveness of the brief online MBI with a two-factor repeated measures ANOVA and explored the effects of TM on the four types of mobile phone addiction with hierarchical linear modeling (HLM) after a brief online MBI.ResultsResults revealed that the experimental group receiving brief online MBI showed a significant decrease in MSNA, MGA, MIAA, and MSVA at the post-test level compared to the pre-test. TM negatively predicted MSNA, MGA, MIAA, and MSVA.DiscussionThe present study found that the brief online mindfulness-based intervention can effectively reduce four types of mobile phone addiction. In addition, the present study revealed that as the levels of TM increased, all four types of mobile phone addiction decreased.